After Ridd: Can Australian Universities Still Regulate Uncivil Behaviours Within Their Institutions? - Levine, Pnina (The University of Western Australia, 2023)
This article provides guidance as to the extent to which Australian universities will need to reconsider behavioural standards previously imposed on staff and students to maintain a collegial and supportive learning and working environment in adopting the Model Code for the Protection of Free Speech and Academic Freedom (‘Model Code’) recommended by former High Court of Australia Chief Justice Robert French. Specifically, it considers the extent to which the Model Code allows universities to regulate staff or student speech where the manner of that speech may be considered to be ‘offensive, shocking or insulting’ as distinct from its content. This analysis involves consideration of the litigation involving Peter Ridd and James Cook University, culminating in the High Court’s decision in Ridd v James Cook University [2021] HCA 32 and some reflections on the Model Code. The article recommends how the Model Code might be amended to provide Australian universities and their staff and students with greater certainty in relation to the extent to which universities can regulate disrespectful and discourteous behaviour within their institutions while still upholding freedom of speech and academic freedom in accordance with the principles of the Model Code.